Cardiac MRI based numerical modeling of left ventricular fluid dynamics with mitral valve incorporated. Issue 7 (3rd May 2016) - Su, Boyang; Tan, Ru San; Tan, Ju Le; Guo, Kenneth Wei Qiang; Zhang, Jun Mei; Leng, Shuang; Zhao, Xiaodan; Allen, John Carson; Zhong, Liang
Abstract: Recent numerical studies were focused on the modeling of flow in patient-specific left ventricle (LV); however, the mitral valve (MV) was usually excluded. In this study, both patient-specific LV and MV were modeled to achieve a more realistic intraventricular flow. Cardiac MRI images were acquired from a pulmonary arterial hypertension (PAH) patient and a healthy volunteer, and manual segmentation was conducted to reconstruct three-dimensional (3D) LV and MV geometries at each frame. Based on these 3D geometries, vortex formation time (VFT) was derived, and the values were 4.0 and 6.5 for the normal subject and the PAH patient, respectively. Based on studies in the literature, VTF in the healthy subject fell within the normal range, while that in the PAH patient exceeded the threshold for normality. The vortex structures in the LV clearly showed that the vortex ring was initiated from the tips of the MV instead of the mitral annulus. The excessive VFT during the rapid filling phase in the PAH patient resulted in a trailing flow structure behind the primary vortex ring, which was not observed in the normal subject. It can be deduced from this study that incorporating the MV into a patient-specific model is necessary to produce more reasonable VFT and intraventricular flow.